Preliminary study on tracing 14C in groundwater-derived dissolved organic carbon: transport, transformation, and seawater recirculation in Jeju Island, South Korea - Fang, Ling; Kim, HeeA; Kim, Jeonghyun; Cheng, Peng; Ryu, Yeongjin; Kim, Guebuem; Kim, Minkyoung (Frontiers in Marine Science, 2025)
Submarine groundwater discharge (SGD) is a key but understudied pathway in the terrestrial-oceanic dissolved organic carbon (DOC) cycle. In this study, fresh and saline groundwater samples were collected from two sites on Jeju Island, South Korea: Hwasun and Bangdu Bay on the western and eastern coast, respectively. DOC concentrations in fresh groundwater were extremely low (5 ± 3 μM), with pre-aged radiocarbon values ranging from –469 to –407‰. In the brackish zone of Bangdu Bay, distinctive spectroscopic signals, elevated DOC concentrations, and enriched Δ14C-DOC values along the groundwater-coastal continuum indicate active recirculation of coastal water. Overall, our findings demonstrate that SGD not only delivers aged terrestrial DOC to coastal waters but is also modified by coastal processes, underscoring its potential significant yet complex role under the influence of coastal pollutions.